Spatiotemporal patterns and drivers of Chl-a in Chinese lakes between 1986 and 2023 - Liu Chang; Zhu Fangfang; Yan Xingguang; Ma Xiaoliang; Yang Di; Smith Andrew Robert (Open Geosciences)
Eutrophication of water bodies is a major ecological problem associated with increased input of nitrogen and phosphorus during rapid economic development. The abundance of chlorophyll-a (Chl-a) in aquatic systems serves as a reliable ecological indicator of lake water quality that is strongly correlated to the degree of eutrophication. Using multi-source remote sensing data – including Landsat and Sentinel-2 imagery – and employing Theil-Sen median analysis, the Mann–Kendall trend test, and Pearson correlation analysis, we comprehensively examined the spatial and temporal dynamics, as well as the driving forces, of Chl-a concentrations in medium and large lakes (lake area >10 km2) across China from 1986 to 2023. The results showed that, over the past four decades, Chl-a concentration in Chinese lakes generally exhibited a declining trend, with a more pronounced decrease occurring after 2013. Significant regional disparities were observed: lakes in the southwestern region demonstrated the most pronounced declines, while those in the southern region exhibited the least. Seasonal variability in Chl-a was consistent across the country, with concentrations peaking between July and August and reaching their lowest levels from November to March. Nevertheless, the extent of seasonal variation differed regionally, being lower in western China and greater in the eastern and southern regions. Land surface temperature, water vapor content, and soil moisture showed strong positive correlations with Chl-a concentrations, while elevation and wind speed displayed negative correlations. These relationships also varied significantly in geographic subregions. Overall, the study revealed the spatiotemporal patterns and driving mechanisms of Chl-a dynamics in Chinese lakes and highlighted the spatial heterogeneity of ecological and geographical influences on Chl-a concentrations.